Reliability of urinary cytology and cystoscopy for the screening and diagnosis of bladder cancer in patients with neurogenic bladder: A systematic review. Issue 3 (19th September 2017) - Alimi, Quentin; Hascoet, Juliette; Manunta, Andrea; Kammerer‐Jacquet, Solène‐Florence; Verhoest, Grégory; Brochard, Charlène; Freton, Lucas; Kerdraon, Jacques; Senal, Nelly; Siproudhis, Laurent; Rioux‐Leclercq, Nathalie; Brucker, Benjamin; et al.
Abstract : Aims: To assess the reliability of urinary cytology and cystoscopy to screen and diagnose bladder cancer in patients with NB. Patients and Methods: A systematic literature search of the Medline and Embase databases was performed in April 2017. Data extraction was performed by two independent reviewers. A narrative synthesis was made. Results: Out of 220 records assessed, 15 were included in this systematic review. All studies were prospective or retrospective series with no control group. Cystoscopy allowed the detection of asymptomatic bladder cancer in 0‐10 patients, with a screening sensitivity (available in only one study) of 0%, a screening specificity ranging from 65% to 90%, and a yield in detecting asymptomatic bladder cancer of 0% in all series where it could be calculated. Urinary cytology allowed the detection of bladder cancer in asymptomatic patients in 0‐12 patients, with a screening sensitivity of 71%, a screening specificity ranging from 92% to 97% and a yield ranging from 0% to 1.25%. Sensitivity of cystoscopy for diagnosis of bladder cancer ranged from 27% to 81% and specificity was 54% in the only study where it could be calculated. Sensitivity of urinary cytology for diagnosis of bladder cancer was 0‐72% and specificity was 100%. Conclusion: There is currently insufficient data to support formal recommendations of using both tools in the screening of bladder cancer in patients with neurogenic bladder. Urinary cytology outperformed cystoscopy for screening and might be the best tool currently available.